Let’s handover our patients to the highest quality of anesthesiology care - Arnaoutoglou, Eleni; Chalkias, Athanasios (Journal of Emergency and Critical Care Medicine, 2018)
Effective communication is one of the most significant skills in medical practice and should be strongly emphasized and taught during pre- and postgraduate training. The World Health Organization has included communication during patient care handovers among its top five patient safety initiatives since 2006 (1). Although it is usually perceived as a ‘physician to patient’ interaction, the definition also includes the ‘physician to physician’ communication. However, the failure of healthcare professionals to communicate is a major problem worldwide. Most preventable adverse events in medicine are because of communication errors, while more than half of these occur in relation to patient handover (2).